Collective dynamics of micro-resistance through CSR by academic activists: Collective autoethnography in a French business school - Joly, Cédrine; Kessari, Myriam; Marais, Magalie; Meyer, Maryline (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2022)
Through a collective autoethnography, we describe how our group of academic activists—four women—has continued to support CSR activities in research and teaching practices and in all aspects of our business school’s operations to resist mainstream management education. We have done so while contesting the business-case approach to CSR and the pressures that threaten to undermine or lessen the importance of social and environmental issues in management education. Here, we describe the forms of resistance that we undertook, our identity work between resistance and compliance in our business school and our collective dynamics over time.